Pengaruh Pelatihan Kerja dan Kompensasi Terhadap Kinerja Pegawai Dinas Pendidikan Kota Makassar - Natsir, Uhud Darmawan; Andini, HS; Ramli, Anwar (CV. Lafadz Jaya, 2023)
The purpose of this study was to determine the effect of job training and compensation on the performance of Makassar City Education Office employees. The subjects in this study were 94 employees working at the Makassar City Education Office. This research is included in quantitative research and quantitative analysis to test the research hypothesis using the IMB SPSS version 25 software. The results of this study indicate that job training and compensation have a positive and significant effect on employee performance. This is evidenced by the t-value of -2.984 where <t-table (1.66177) and a significance value of 0.000 <0.05. The results of the study show that job training and compensation have a positive and significant effect on employee performance. This is evidenced by the calculated F value of 25.204 > 3.10 and a significance value of 0.000 <0.05.